Probing cytoskeletal modulation of passive and active intracellular dynamics using nanobody-functionalized quantum dots - Eugene A. Katrukha (Nature Portfolio, 2017)
Methods to probe transport dynamics within cells can shed insight into the nature of the cytoplasm. Here the authors develop a method to functionalize and deliver quantum dots intracellularly to show how the cytoskeleton influences non-equilibrium intracellular transport dynamics.